Pengaruh substitusi tepung ikan lele (Clarias sp) dan tepung kacang hijau (Vigna radiata) terhadap daya terima biskuit - Lopo, Valencia; Sine, Juni Gressilda Louisa; Niron, Maria F. Vinsensia D.P. Kewa (Poltekkes Kemenkes Kupang, 2025)
To achieve optimal growth and development, it is important to consider the golden age, often referred to as the vital development phase for children. According to the 2023 Indonesian Health Survey (SKI), 9.4% of children in East Nusa Tenggara (NTT) province are underweight. Therefore, researchers decided to investigate the impact of replacing catfish flour with green bean flour on biscuit acceptance. The objective of this study was to determine the nutritional components and biscuit acceptance test of biscuits made using green bean flour as a substitute for catfish flour. This study is an experimental study, with food formulations using proportions of catfish flour (10%, 20%, 30%) and green bean flour (30%, 20%, 10%). Acceptance test data were analyzed descriptively, using the Normality Test, ANOVA, and Tukey's Test. It can be concluded that the preference level for each treatment received a score of 4, indicating preference. Based on statistical analysis, there was a significant difference in taste between treatments P0 and P3. The macronutrient values of the biscuits, with varying proportions of catfish flour to green bean flour, were affected (energy, protein, fat, and carbohydrates). To prevent cross-contamination from the environment, researchers are advised to use an oven when drying the green beans and catfish, and to use uniform molds to ensure consistent product weight.